Associations between Heat-Stable (O) and Heat-Labile (HL) Serogroup Antigens of Campylobacter jejuni: Evidence for Interstrain Relationships within Three O/HL Serovars - Jackson, C. J. (American Society for Microbiology, 1998)
A comparative examination of the heat-stable (O) and heat-labile (HL) serogrouping results for 9,024 sporadic human isolates of Campylobacter jejuni revealed conserved associations between specific O and HL antigens (O/HL serovars). Forty-nine percent of the isolates which grouped for both O and HL antigens belonged to one of three serovars: O 4 complex/HL 1 (17.9%), O 1/HL 2 (16.8%), or O 50/HL 7 (14.5%). Other common serovars were O 2/HL 4 (8.3%), O 6/HL 6 (8.1%), O 53/HL 11 (4.5%), O 19/HL 17 (3.3%), O 5/HL 9 (3.3%), O 9/HL 9 (3.2%), and O 23/HL 5 (3.1%). These 10 serovars accounted for 83.1% of the serogroupable isolates. A large number of strains (41.3%) could be typed by only one of the two methods or could not be serogrouped (11%). Strains belonging to three serovars, O 2/HL 4, O 50/HL 7, and O 23/HL 5, were further characterized by combining data from expressed features (O/HL serogroups, phage groups, and biotypes) with restriction fragment length polymorphism genotypes. These polyphasic data demonstrated that within each serovar, individual isolates showed substantial conservation of both genomic and phenotypic characteristics. The essentially clonal nature of the three serovars confirmed the potential of combined O and HL serogrouping as a practical and phylogenetically valid method for investigating the epidemiology of sporadic C. jejuni infection.